Impact of Demographics on Consumer Preferences in Online Shopping: An Analysis of Age, Gender, and Education Factors - Jainish Gami; Nirav Patel; Vibhu Aghera; Nishit Patel; Manthan Gondaliya; Rahul Chauhan; Andino Maseleno (Greenation International Journal of Economics and Accounting, 2023)
This study explores the influence of demographic factors-age, gender, and education level-on consumer preferences and behaviors in online shopping. Through a quantitative analysis using ANOVA, data from 119 participants highlight that age and education level significantly impact perceptions of platform selection, product security, and the importance of reviews, while gender differences are less pronounced. Key findings indicate that younger consumers value convenience and variety, while higher-educated users prioritize security and trust in reviews. These insights are critical for e-commerce platforms aiming to enhance user experience and drive engagement by aligning their strategies with demographic-specific needs. The study provides a foundation for further research on evolving consumer behaviors and offers global relevance as e-commerce continues its rapid expansion.